For which infants with viral bronchiolitis could it be deemed appropriate to use albuterol, at least on a therapeutic trial basis? (2021)
Although there is increasing evidence showing that infants with viral bronchiolitis exhibit a high degree of heterogeneity, a core uncertainty shared by many clinicians is with regard to understanding which patients are most likely to benefit from bronchodilators such as albuterol. Based on our review, we concluded that older infants with rhinovirus (RV) bronchiolitis, especially those with a nasopharyngeal microbiome dominated by Haemophilus influenzae; those affected during nonpeak months or during non-respiratory syncytial virus (RSV) predominant months; those with wheezing at presentation; those with clinical characteristics such as atopic dermatitis or a family history of asthma in a first-degree relative; and those infants infected with RSV genotypes ON1 and BA, have the greatest likelihood of benefiting from albuterol. Presently, this patient profile could serve as the basis for rational albuterol administration in patients with viral bronchiolitis, at least on a therapeutic trial basis, and it could also be the starting point for future targeted randomized clinical trials (RCTs) on the use of albuterol among a subset of infants with bronchiolitis.